A Multidisciplinary Study of Eye Tracking Technology for Visual Intelligence - Shyamli Sindhwani; Gregory Minissale; Gerald Weber; Christof Lutteroth; Anthony Lambert; Neal Curtis; Elizabeth Broadbent (MDPI AG, 2020)
The ability to analyse aspects of visual culture-works of art, maps or plans, graphs, tables and X-rays-quickly and efficiently is critical in decision-making in a broad range of disciplines. Eye tracking is a technology that can record how long someone dwells on a particular detail in an image, where the eye moves from one part of the image to the other, and the sequence the viewer uses to interpret visual information. These MP4 recordings can be played back and graphically enhanced with coloured dots and lines to point out this natural and fluent eye behaviour to learners. These recordings can form effective pedagogical tools for learning how to look at images through the eyes of experts by mimicking the patterns and rhythms of expert eye behaviour. This paper provides a meta-analysis of studies of this kind and also provides the results of a cross-disciplinary project which involved five different subject areas. The consensus arising from our meta-analysis reveals an emerging field with broad concerns in need of more integrated research. None of the studies cited in this article are interdisciplinary across the sciences and arts and, while some of them address higher education in medicine and computing, there are no interdisciplinary studies of how eye tracking is important for teaching in arts and science subjects at undergraduate and postgraduate levels. In addition, none of the studies address how learning practitioners find these eye recordings useful for their own understanding of learning processes. This establishes the unique contribution of this project.